The Role of Human Papillomavirus in Oral Carcinogenesis - Simonato, Luciana Estevam (2007)
Recent studies using new viral detection technologies point to human papillomavirus (HPV) as the etiological agent of uterine cervical cancer. Other anatomical sites besides the genital area can be infected by HPV, mainly the head and neck. The direct involvement of HPV in oral carcinoma has still not been fully proven, but its synergism with chemical and physical carcinogens in some squamous cell carcinomas appears to be the most likely explanation for the role of HPV in oral carcinogenesis.